2012
DOI: 10.4049/jimmunol.1103087
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Basic Protein-Specific TCR/HLA-DRB5*01:01 Transgenic Mice Support the Etiologic Role of DRB5*01:01 in Multiple Sclerosis

Abstract: Genetic susceptibility to multiple sclerosis (MS) has been linked to the HLA-DR15 haplotype consisting of DRB1*15:01(DR2b)- and DRB5*01:01(DR2a) alleles. Given almost complete linkage disequilibrium of the two alleles, recent studies have suggested differential roles in susceptibility (DR2b) or protection from MS (DR2a). Our objective was to assess the potential contribution of DR2a to disease etiology in MS using a humanized model of autoimmunity. To assess the potential contribution of DR2a to disease etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 62 publications
0
45
0
1
Order By: Relevance
“…Female C57BL/6J (Jackson Labs) or SJL/J (Harlan Laboratories) mice were acclimatized at least one week prior to study and then used as models of active chronic and passive relapsing-remitting model of MS, respectively. 8–10 week old C57BL6/J mice were immunized with 200 ÎŒg MOG35-55 (MEVGWYRSPFSRVVHLYRNGK; Stanford Pan Facility, Stanford CA) as described previously (Quandt et al, 2012). For passive disease, animals were immunized with 75 ”g PLP139-151 (HCLGKWLGHPDKF, Stanford Pan Facility) and draining lymph node (LN) cells enriched with PLP before transfer to healthy recipients as described (Anderson et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Female C57BL/6J (Jackson Labs) or SJL/J (Harlan Laboratories) mice were acclimatized at least one week prior to study and then used as models of active chronic and passive relapsing-remitting model of MS, respectively. 8–10 week old C57BL6/J mice were immunized with 200 ÎŒg MOG35-55 (MEVGWYRSPFSRVVHLYRNGK; Stanford Pan Facility, Stanford CA) as described previously (Quandt et al, 2012). For passive disease, animals were immunized with 75 ”g PLP139-151 (HCLGKWLGHPDKF, Stanford Pan Facility) and draining lymph node (LN) cells enriched with PLP before transfer to healthy recipients as described (Anderson et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, EAE is experimentally induced (as the acronym implies) using antigens (peptides and proteins) along with bacterially-derived adjuvants; spontaneous disease is achieved using transgenic mice models (Madsen et al, 1999; Quandt et al, 2012). Moreover, while both humoral (B cells, plasma cells and antibody) and cellular (CD4 + and CD8 + ) mechanisms have been shown to contribute to MS immunopathology (Lassman et al, 2007; Simmons et al, 2013 May 21), EAE represents the prototype T cell-mediated autoimmune model, whereby CD4 + T cells are the predominant effector cell in the disease, which is largely driven by a pro-inflammatory Th 1 /Th 17 cytokine milieu (Kroenke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This region is in very strong linkage disequilibrium (LD). DR alpha chain and the two beta chains creates the two functional surface heterodimers, DR2b (DRA*0101, DRB1*1501) and DR2a (DRA*0101, DRB5*0101) [30]. Whether both or only one of the two alleles and resulting DR molecules contribute to MS etiopathogenesis are one of the most important questions in MS researches.…”
Section: Discussionmentioning
confidence: 99%
“…The present of antigens from outside of the cell to T-lymphocytes is the function of HLAs class II and it contains the classical alpha and beta chain genes including DP, DM, DOA, DOB, DQ , and DR. As Class II molecules can bind and present certain self-peptides, several studies indicated that HLAs class II have been associated to several autoimmune or immune mediated disorders, including MS [29]. An estimated 10-60% of the MS genetic risk appears to be conferred by the DR15 haplotype (DQB1*0602, DQA1*0102, DRB1*1501, DRB5*0101) [30]. Although several studies have been carried out on the association of HLA DRB5*01 with MS in various populations [31][32][33][34], there is no data about this issue in Khuzestan province in Iran.…”
Section: Introductionmentioning
confidence: 99%